2013
DOI: 10.3144/expresspolymlett.2013.31
|View full text |Cite
|
Sign up to set email alerts
|

Reactive processing of maleic anhydride-grafted poly(butylene succinate) and the compatibilizing effect on poly(butylene succinate) nanocomposites

Abstract: Abstract. In this study, maleic anhydride-grafted poly(butylene succinate) (PBS-g-MA) was synthesized via reactive meltgrafting process using different initiator contents. The grafting efficiency was increased with the initiator content, manifested by the higher degree of grafting in PBS-g-MA. The grafting reaction was confirmed through Fourier transform infrared (FTIR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy. Then, PBS-g-MA was incorporated into organo-montmorillonite (OMMT) filled poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 52 publications
11
73
1
1
Order By: Relevance
“…2(b), neat PBS showed double melting peaks, due to two different crystal structures, at 100.78 (T m1 ) and 112.93 (T m2 ). Vega-Baudrit et al [17,31] explained that lower endotherm (T m1 ) is relates to the melting of the original crystallites and higher endotherm (T m2 ) corresponds to the melting of the recrystallized one. With increasing the thymol content, both T m1 and T m2 tended to shifted but only minutely.…”
Section: Barrier and Thermal Properties Pbs/thymol Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…2(b), neat PBS showed double melting peaks, due to two different crystal structures, at 100.78 (T m1 ) and 112.93 (T m2 ). Vega-Baudrit et al [17,31] explained that lower endotherm (T m1 ) is relates to the melting of the original crystallites and higher endotherm (T m2 ) corresponds to the melting of the recrystallized one. With increasing the thymol content, both T m1 and T m2 tended to shifted but only minutely.…”
Section: Barrier and Thermal Properties Pbs/thymol Filmsmentioning
confidence: 99%
“…Finally, samples were cooled to room temperature. The degree of crystallinity (X c ) was calculated by using Equation (1) [17].…”
Section: Testing and Characterizationsmentioning
confidence: 99%
“…The characteristic peaks of the monomers are: (i) a broad peak in the region around 3300 cm −1 , corresponding to the OH stretching of the carboxylic acid group; (ii) a peak at 1678 cm −1 , which is in the range of 1710–1665 cm −1 , characteristic of the carboxylic acid group; (iii) an intense and broadband in the region from 3200 to 3500 cm −1 , related to stretching of the alcohol group. As one can see, the characteristic FTIR peaks of the monomers were replaced by the different FTIR peaks of the reaction product . As the polymer product is a polyester, peaks are expected in the region from 1144 to 1264 cm −1 , corresponding to the stretching of the COC bonds of the ester groups; and at 1713 cm −1 , which is related to the stretching of CO bonds of the carbonyl group.…”
Section: Resultsmentioning
confidence: 98%
“…1 H‐NMR spectra of the reaction product are shown in Figure . Phua et al reported the characteristic resonance signals of PBS samples produced through bulk polymerizations, at 2.63 ppm (corresponding to the methylene protons of SA units), at 1.71 ppm (corresponding to the central protons of methylene units of 1,4‐BD) and 4.12 ppm (corresponding to the terminal protons of methylene units of 1,4‐BD). These are the same peaks shown in Figure , indicating the successful formation of PBS.…”
Section: Resultsmentioning
confidence: 99%
“…These additives can be used to boost the physical properties, including thermal stability [1,2], mechanical properties [3][4][5][6][7][8] and flammability [9][10][11] compared with those of neat polymers. Arunvisut et al examined LDPE/MMT nanocomposites with LDPE, organo-clay, PE-g-MA as the compatibilizer and observed that presence of PE-g-MA improves dispersion of exfoliation, tensile modulus, and yield strength as the MMT content increases [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%